The Importance of Sexually Transmitted Diseases and Psychological Child’s Painting Drawings in the Diagnosis of Sexual Abuse Towards the Child - Ekizoğlu, Oğuzhan; Sözen, Mehmet Şevki; Tüzün, Birgül; Korur, Şebnem; Yurtbay, Tülin (The Bulletin of Legal Medicine, 2010)
The sexual abuse of children causes both physical and emotional effects and in this kind of cases, anogenital trauma findings are investigated primarily. In a sexual action that involves the child, although it’s not commonly seen, sexually transmitted diseases and the interpretation of the abuse related painting related that made by child during the physiological evaluation are important in the diagnosis. For this purpose a 13 year old boy who is diagnosed as anogenital herpes is reported with the paintings that are made by him during the physiological evaluation this support abuse. Key words: Sexually abused children, herpes simplex virus, human figure drawings